The mouse Gene Expression Database (GXD): updates and enhancements - Hill, David P. (Oxford University Press, 2004)
The Gene Expression Database (GXD) is a community resource for gene expression information in the laboratory mouse. By collecting and integrating different types of expression data, GXD provides information about expression profiles in different mouse strains and mutants. Participation in the Gene Ontology (GO) project classifies genes and gene products with regard to molecular functions, biological processes, and cellular components. Integration with other Mouse Genome Informatics (MGI) databases places the gene expression information in the context of mouse genetic, genomic and phenotypic information. The integration of these types of information enables valuable insights into the molecular biology that underlies development and disease. The utility of GXD has been improved by the daily addition of new data and through the implementation of new query and display features. These improvements make it easier for users to interrogate and visualize expression data in the context of their specific needs. GXD is accessible through the MGI website at http://www.informatics.jax.org/ or directly at http://www.informatics.jax.org/menus/expression_menu.shtml.